2022
DOI: 10.3389/fcvm.2021.761520
|View full text |Cite
|
Sign up to set email alerts
|

The Nonlinear Relationship Between Total Bilirubin and Coronary Heart Disease: A Dose-Response Meta-Analysis

Abstract: Background: Evidence suggests that the total bilirubin has a protective effect on coronary heart disease (CHD), but the dose-response relationship remains controversial, and there is no meta-analysis to assess the relationship.Methods: As of October 1, 2021, relevant literature was selected from four databases (PubMed, Web of Science, Cochrane Library, and Embase) by using a retrieval strategy. The dose-response curve between the total bilirubin and CHD was fitted by a restricted cubic spline. Stata 12.0 was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“… 9 Furthermore, unconjugated bilirubin functions intracellularly, as a potent inhibitor of NADPH oxidase complexes and albumin-bound bilirubin contributes significantly to the oxidant scavenging activity of plasma and may also potentially reduce endothelial dysfunction, which is strictly related to cardiovascular disease and total death. 3 , 4 , 10 Similar inverse associations have now been shown between serum total bilirubin concentrations and coronary artery disease, 11 coronary heart disease, 12 peripheral vascular disease, 13 and stroke. 14 Moreover, mildly elevated total bilirubin (TBIL) concentrations may protect against cardiovascular and total death.…”
Section: Introductionsupporting
confidence: 54%
“… 9 Furthermore, unconjugated bilirubin functions intracellularly, as a potent inhibitor of NADPH oxidase complexes and albumin-bound bilirubin contributes significantly to the oxidant scavenging activity of plasma and may also potentially reduce endothelial dysfunction, which is strictly related to cardiovascular disease and total death. 3 , 4 , 10 Similar inverse associations have now been shown between serum total bilirubin concentrations and coronary artery disease, 11 coronary heart disease, 12 peripheral vascular disease, 13 and stroke. 14 Moreover, mildly elevated total bilirubin (TBIL) concentrations may protect against cardiovascular and total death.…”
Section: Introductionsupporting
confidence: 54%
“…The paradoxical conclusions may be related to the exposure levels and types of bilirubin in the studied objects. For example, a U-shaped relationship between bilirubin and CHD was reported; that is, TB levels within the range of 12–16 µmol/l had the strongest protective effect on CHD ( 9 , 28 , 29 ). Furthermore, Chen and colleagues ( 30 ) analyzed the associations of different types of bilirubin (D-BIL, I-BIL, and TB) with diabetic foot (DF) separately and discovered that serum I-BIL, but not TB and D-BIL, played a protective role in DF, and I-BIL and TB but not D-BIL were independent risk factors for the severity of DF.…”
Section: Discussionmentioning
confidence: 99%
“…Bilirubin, one of the final products of heme metabolism and long considered merely as a toxic waste, has been known for its strong antioxidant, anti-inflammatory, and neuroprotective activities in recent decades ( 1 5 ). As a result, many studies focused on the associations between serum bilirubin levels and chronic inflammatory diseases such as ischemic arterial diseases, especially coronary heart disease (CHD), but with controversial conclusions ( 6 10 ). For example, some studies found that serum bilirubin was negatively related to clinically manifested cardiovascular disease and events ( 6 8 ), whereas others discovered a U-shaped correlation between bilirubin levels and the risk of CHD ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, several studies have revealed a U-shaped association between total bilirubin concentration and coronary heart disease [ 39 , 40 ], telomere length [ 41 ], and all-cause mortality [ 42 ]. These findings suggest bilirubin’s threshold effect on bone health.…”
Section: Discussionmentioning
confidence: 99%